Figuring grief : Gallant, Munro and the poetics of elegy - Smythe, Karen, 1962- (McGill-Queen's University Press, 1992)
The title, Figuring Grief, refers to the narrative process whereby mourning is depicted. In her textual analysis, Smythe explores various connections between representation and consolation. Drawing on genre and narratological theory, she outlines the development of the "fiction-elegy" as a sub-genre and suggests that the modernist writings of Woolf and Joyce are paradigmatic examples of the form. She then uses these paradigms as suggestive "reading models" for the interpretation of works by Gallant, Munro, and other contemporary fiction-elegists. Figuring Grief offers new readings of specific works and suggests that new ways of reading are both demanded and rewarded by a poetics of elegy.